2021
DOI: 10.1002/hed.26882
|View full text |Cite
|
Sign up to set email alerts
|

A national study of health‐related quality of life in patients with cancer of the base of the tongue compared to the general population and to patients with tonsillar carcinoma

Abstract: Background: This exploratory, registry-based, cross-sectional study aimed to evaluate patients' health-related quality of life (HRQOL) in a subsite of oropharyngeal cancer: cancer of the base of the tongue (CBT).Methods: CBT patients, treated with curative intent, completed the EORTC QLQ-C30 and QLQ-H&N35 questionnaires 15 months after diagnosis. The HRQOL of CBT patients was compared to reference scores from the general population and to that of tonsillar carcinoma patients. Results: The 190 CBT patients scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Berg performed a cross-sectional study comparing BOT cancer patients (n = 190) to tonsillar cancer patients (n = 405) and to the general population (n = 190) [ 30 ]. This research identified better emotional function in the patients with HPV-associated OSPCC than in the HPV-negative patients on the EORTC QLQ-C30.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Berg performed a cross-sectional study comparing BOT cancer patients (n = 190) to tonsillar cancer patients (n = 405) and to the general population (n = 190) [ 30 ]. This research identified better emotional function in the patients with HPV-associated OSPCC than in the HPV-negative patients on the EORTC QLQ-C30.…”
Section: Resultsmentioning
confidence: 99%
“…Berg did not identify any significant difference in social domain of the EORTC QLQ-C30 or in the EORTC QLQ-HN35 scores in BOT OPSCC patients who underwent different treatment modalities [ 30 ]. Kaffenberger did not identify differences in UW-QOL social scores when comparing CRT to surgery with adjuvant RT or CRT [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations